(untitled) (Baghdad Science Journal, 2025)
This search reports the synthesis of some new series of Schiff base compounds for trimetheprim derivatives which known high been known as a medicinal effectiveness. Trimetheprim was condensed with several substituted aldehydes compounds.(4-dimethyl amine benzaldehyde , propanal , salicaldehyde, 2.4 dimethoxy benzaldehyde and 4- methyl benzaldehyde) to obtain Schiff base products(1a-5a) and several substituted ketones compound (4-aminoacetophenone,4-chloroacetophenone, isobutyleketone, acetylacetone and acetophenone) to obtain Schiff base products(6b-10b) in ethanol in the presence of concentrated sulphuric acid as a catalyst to yield the Schiff base. The structure of synthesized compounds has been established on the basis of their Chemical structures of all products were confirmed by spectrophotometric methods such as U.V. visible and FTIR.. All these compounds were evaluated for their antibacterial activity in vitro against Gram + ve bacteria (bacillus) , Gram –ve bacteria (E-Coli).Most Compound under investigation exhibited potent antibacterial activity